Dengue em localidade urbana da região sudeste do Brasil: aspectos epidemiológicos Dengue in urban locality of Southeastern, Brazil: epidemiological aspects - Ricardo J. S. Pontes; Antonio Ruffino-Netto (Universidade de São Paulo, 1994)
Foram revistos alguns aspectos da epidemiologia do dengue, como parte do estudo de epidemia ocorrida no Município de Ribeirão Preto, Estado de São Paulo, no período de novembro de 1990 a março de 1991. Deu-se ênfase aos fatores envolvidos no risco de ocorrência do dengue hemorrágico/síndrome de choque do dengue. Traçou-se um quadro de referência a respeito do comportamento epidemiológico do dengue através do tempo e em diferentes áreas geográficas. A epidemia de Ribeirão Preto foi situada no contexto da progressão do dengue em nível mundial, nas Américas, e particulamente no Brasil e Estado de São Paulo. A dengue fever epidemic which occurred in Ribeirão Preto County, S. Paulo State, Brazil, during the period November, 1990 to March, 1991 has been analysed else where. The general aspects of dengue epidemiology and control have been reviewed in this article. Emphasis is given to the analysis of some factors involved in the risk of dengue haemorrhagic fever and ecological aspects of the vector, as well as to the appropriateness of strategies for dengue eradication or control. Epidemiological characteristics of dengue, mainly those related to its occurrence in different geographical areas and periods of time are described. The Ribeirão Preto epidemic has thus, been set within the context of the spread of the disease at global level, in the Americas, and particularly in Brazil and S. Paulo State.